RETRACTED: FACTOR MODEL ASSESSMENT OF THE COMPETITIVE INNOVATION CLUSTERS ELECTRONICS BASED ON ANALYSIS OF THE STAGES OF THEIR LIFE CYCLE - A. V. Brykin; K. A. Kolegov (Модернизация, инновация, развитие, 2015)
Retracted articleThe cluster principle development in the world of electronics is one of the most effective examples of high-tech industry. The author considers the possibility of using clusters to modernize the Russian economy.